Glucopyranose spirohydantoins: Specific inhibitors of glycogen phosphorylase - delaFuente, C; Krulle, T; Watson, K; Gregoriou, M; Johnson, L; Tsitsanou, K; Zographos, SE; Oikonomakos, N; Fleet, G (1997)
A short synthesis of the spirohydantoin of glucopyranose 1β [a potent and specific inhibitor of glycogen phosphorylase], together with its inactive anomer 1α, from a readily available heptonolactone is described; this is the first synthesis of a spirohydantoin of a pyranose in which the pyranose ring is formed after the hydantoin ring.